A Feature Extraction Technique Based on Factor Analysis for Pulsed Eddy Current Defects Categorization - Latif, N.A.A. (Institute of Physics Publishing, 2019)
Pulsed eddy current (PEC) is an advance Non-destructive testing that is widely used in multiple industries for surface and subsurface defect detection. Normally, the conventional features extractions are conducted based on time to peak and peak value response. However, signals extraction could be a confusing for a thin specimen because times to peak for both surface and subsurface defects are occurred at almost similar time. This paper introduced the application of confirmatory Factor Analysis for defect categorizing for stainless steel thin plate. Through this statistical method, two categories of defects namely surface and subsurface defects are clearly to be distinguished between one to another. Â© Published under licence by IOP Publishing Ltd.